2019
DOI: 10.1016/j.cocis.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Protein-surface interactions at the nanoscale: Atomistic simulations with implicit solvent models

Abstract: A full molecular-level understanding of protein adsorption in important situations such as the formation of protein films at solid/liquid interfaces or the formation of a protein corona over inorganic nanoparticles is still lacking. All-atomic implicit solvent molecular dynamics (MD) simulations, which are successfully employed in many related protein studies (such as protein folding for example) are emerging also as a useful tool to investigate proteins at surfaces. Implicit solvent simulations replace the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…A review of the method can be found in ref. 26 All MD simulations were performed by using the NAMD 2.12 software. 46 In these simulations the Newton equations of motion were solved numerically with a time-step of 2 fs.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
See 2 more Smart Citations
“…A review of the method can be found in ref. 26 All MD simulations were performed by using the NAMD 2.12 software. 46 In these simulations the Newton equations of motion were solved numerically with a time-step of 2 fs.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…The systems MD3 and MD6 were further simulated for ~12,000,000 steps (note that due to the use of implicit solvent, the kinetics of the simulation cannot be easily related to real, physical time. 26 In the case of the NP with 9 nm of diameter (simulation MD9), this method proved to be computationally very expensive, so we employed an alternative approach. We generated an initial configuration of pre-adsorbed proteins using the program packmol.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
See 1 more Smart Citation
“…where N i is the number of molecules in the interaction zone. Finally, the probability density of fibrinogen molecule adsorption at a given point at the interface was calculated from the Boltzmann formula: ρ p v = e −φ a /kT (7) Using this algorithm, three various adsorption regimes were efficiently modeled (see Supporting Information): (i) the exclusively side-on regime, (ii) the end-on regime, and (iii) the mixed regime where the molecules can adsorb in the end-on orientation if there is not enough space for the side-on orientation. The most relevant quantities derived from the modeling were the numbers of adsorbed fibrinogen molecules forming the corona in the side-on N p and the end-on N p⊥ orientations [9].…”
Section: Theoretical Modelingmentioning
confidence: 99%
“…[1][2][3][4]. In the case of nanoparticle carriers, a controlled protein attachment leads to the "corona" formation extensively studied for single-molecule systems and for mixtures comprising the blood serum [5][6][7][8]. However, because of relatively low stability, nanoparticles decorated by coronas are difficult to study by conventional techniques, which require suspension centrifugation or filtration.…”
Section: Introductionmentioning
confidence: 99%